2022
DOI: 10.3389/fmed.2022.834106
|View full text |Cite
|
Sign up to set email alerts
|

Covered TIPS Procedure-Related Major Complications: Incidence, Management and Outcome From a Single Center

Abstract: Background and ObjectiveTransjugular intrahepatic portosystemic shunt (TIPS) is a well-established procedure for treating complications of portal hypertension. Due to the complexity of anatomy and difficulty of the puncture technique, the procedure itself might brought potential complications, such as puncture failure, bleeding, infection, and, rarely, death. The aim of this study is to explore the incidence, management, and outcome of TIPS procedure-related major complications using covered stents.MethodsPati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It is achieved successfully in more than 90% of cases. TIPS complications can be classified as related to the procedure or the stent and are around 3% but reported as 20%, with derived mortality at 0.84% [ 3 , 4 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is achieved successfully in more than 90% of cases. TIPS complications can be classified as related to the procedure or the stent and are around 3% but reported as 20%, with derived mortality at 0.84% [ 3 , 4 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Yin et al. [9] reported that the incidence of major post-TIPS complications occurred in about 3.2% of patients while 0.74% experienced hemoperitoneum out of a total of 948 patients. In yet another study by Dariushnia et al.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Griffin et al. reported that out of 71 patients who underwent the TIPS procedure, inadvertent puncture of the liver capsule occurred in 4 patients, with one of them developing hemoperitoneum [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Procedural complications during TIPS are rare (<5%) in contemporary series 45,46 but may include intraperitoneal bleeding, arterial injury, liver infarct, hepatic capsular puncture, hemobilia, immediate TIPS thrombosis, and sepsis 47,48 . Procedure-related deaths occur in <1% 46 …”
Section: Tipsmentioning
confidence: 99%